PENERAPAN MODEL PROBLEM BASED LEARNING MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA SMP NEGERI 1 RANTEPAO - Eka - Aprianti; Sumargiyani Sumargiyani (SIGMA, 2023)
This research is a classroom action research that aims to determine student learning outcomes after implementing the action through a problem based learning. The subjects of this study were class VIII.1 students of SMP Negeri 1 Rantepao in the Even Semester of the 2021/2022 Academic Year with a total of 31 students consisting of 5 boys and 26 girls. This research was carried out in two cycles where each cycle was carried out in two meetings including tests at the end of each cycle. Data collection was carried out by means of learning outcomes tests at the end of each cycle, and observations were made each time the learning process took place. The results obtained after the implementation of the action through the problem based learning two cycles are: a) Improving student learning outcomes. This can be seen from the increase in the average score of mathematics learning outcomes, namely in the first cycle of 77.51 with classical learning mastery of 67.7% then increasing in the second cycle to 85.16 with classical learning mastery of 87%. b) An increase in student activity in the learning process in accordance with the results of observations made during the study. From the results of the analysis it can be concluded that the problem based learning can improve the mathematics learning outcomes of class VIII.1 students of SMP Negeri 1 Rantepao.